2018
DOI: 10.13004/kjnt.2018.14.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Anterior Cervical Fusion Using Polyetheretherketone Cage with Demineralized Bone Matrix and Plate for Management of Subaxial Cervical Spine Injuries

Abstract: ObjectiveWe evaluated the usefulness of a polyetheretherketone (PEEK) cage filled with demineralized bone matrix (DBM) and plate fixation in anterior interbody fusions for subaxial cervical spine injuries.MethodsA retrospective review of 98 patients (58 women, 40 men; mean age, 49.7 years; range, 17–78 years) who underwent single-level anterior cervical discectomy and fusion (ACDF) using a PEEK cage filled with DBM and plate fixation for subaxial cervical spine injuries from March 2005 to June 2018 was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…In our study, the use of DBM was found to be associated with an increased swelling. However, Other studies have reported that the use of DBM is not significantly associated with the occurrence of complications, such as swelling and dysphagia [ 12 , 16 ]. This discrepancy may be attributed to the differences in sample sizes between our study and previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the use of DBM was found to be associated with an increased swelling. However, Other studies have reported that the use of DBM is not significantly associated with the occurrence of complications, such as swelling and dysphagia [ 12 , 16 ]. This discrepancy may be attributed to the differences in sample sizes between our study and previous research.…”
Section: Discussionmentioning
confidence: 99%
“…About 89% of the patients with preoperative radiculopathy improved and were without symptoms on follow-ups. Han et al 16 considered the follow-up 27.6 months, where one Frankel grade improvement was observed in 21 cases (21.4%). This study showed complete fusion in all of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cagealone fusion of the single segment has been reported not to be inferior in the clinical progress in comparison with ACDF combining both cage or spacer and plate and screw fixation, however in the case of multiple segments, ACDF combining both cage or spacer and plate and screw fixation shows more stable clinical and radiologic results than cagealone fusion 1,6,14,39) . A plate can be used with cages or spacers made of various materials such as titanium, PEEK, and allobone and can be used by packing bone materials inside 10,32,40) . In some cases, it is used only as a spacer made in a mesh form and inserted simply.…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) and titanium cages may be used as stand-alone for a single-level cervical disc disease, however the incidence of subsidence and non-union is high multi-level cervical disc diseases of 2 or more levels, making it difficult to expect stable bone fusion 4,12,35,38) . Therefore, rather than stand-alone cage fusion, surgery to transplant a bone substitute into interbody space by packing it in a spacer or cage and to induce stable bone fusion by reinforcing the fixation force with the plate and screw fixation in recent years 10,33,40) . Allograft cervical spacer is the most commonly used implant material and shows a relatively stable fusion rate, however various problems such as spacer breakage, subsidence, dislodgement, and non-union occur in the process of bone fusion, resulting in relatively moderate clinical results such as delayed bone fusion and axial pain, as well as serious severe complications such as re-operation 25,31,41) .…”
Section: Introductionmentioning
confidence: 99%